2017
DOI: 10.1128/aem.02751-16
|View full text |Cite
|
Sign up to set email alerts
|

LacI Transcriptional Regulatory Networks in Clostridium thermocellum DSM1313

Abstract: Organisms regulate gene expression in response to the environment to coordinate metabolic reactions. Clostridium thermocellum expresses enzymes for both lignocellulose solubilization and its fermentation to produce ethanol. One LacI regulator termed GlyR3 in C. thermocellum ATCC 27405 was previously identified as a repressor of neighboring genes with repression relieved by laminaribiose (a ␤-1,3 disaccharide). To better understand the three C. thermocellum LacI regulons, deletion mutants were constructed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…Moreover, the genome of C. thermocellum may harbor additional as-yet-unidentified σ I -dependent promoters that may be activated by more than one σ I factor. Therefore, during future studies of a particular σ I factor directly in C. thermocellum , we could expect a cascade of interactions among the different σ I s. Additionally, cellulosomal component genes can also have σ A -dependent promoters 11 , 43 and other regulatory proteins 44 , making the analysis of σ I s directly in C. thermocellum more complex. If these observations are not taken into account during the direct analysis of σ I s in C. thermocellum , the results obtained can be misinterpreted.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the genome of C. thermocellum may harbor additional as-yet-unidentified σ I -dependent promoters that may be activated by more than one σ I factor. Therefore, during future studies of a particular σ I factor directly in C. thermocellum , we could expect a cascade of interactions among the different σ I s. Additionally, cellulosomal component genes can also have σ A -dependent promoters 11 , 43 and other regulatory proteins 44 , making the analysis of σ I s directly in C. thermocellum more complex. If these observations are not taken into account during the direct analysis of σ I s in C. thermocellum , the results obtained can be misinterpreted.…”
Section: Discussionmentioning
confidence: 99%
“…Zverlov et al observed IS 1447 transposition in the genome of C. thermocellum ATCC27405 under chemical mutagenetic stress induced by ethyl-methanesulfonate [ 24 ]. Wilson et al also detected the insertion of an IS 3 element, which may be IS 1447 , in the genome of C. thermocellum DSM1313 during targeted gene deletions using the hypoxanthine phosphoribosyl transferase gene as the counterselection marker [ 57 ]. There could be transposition precedence for the active IS 1447 with the presence of exotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was isolated from 50 ml of chemostat sample using the procedures described in [ 54 ], and quantity and quality were determined using a Nanodrop instrument (ThermoFisher Scientific Waltham, MA). Depletion, library preparation and sequencing were completed at the Joint Genome Institute (JGI, Walnut Creek, CA).…”
Section: Methodsmentioning
confidence: 99%